"MODERN DATABASE MANAGEMENT METHODS " - Jurayev Utkir Murodullo ugli (Zeta Repository, 2023)
The article describes the main concepts of databases and database management systems. Studied classification databases, identified the advantages and disadvantages of data models. Covers modern database management system.